Factors Influencing Decision Making on Occupational Development by Dairy Farmers in Upper Northern Thailand - Prapatigul, Panuphan; Sreshthaputra, Suraphol; Intaruccomporn, Wallratat; Opatpatanakit, Avorn (Kasetsart Journal of Social Sciences, 2011)
The objectives of this research were to study the influence of personal characteristics, socio-economic factors, and dairy farming factors on decision making on occupational development by dairy farmers in upper northern Thailand. The study sample consisted of 289 dairy farmers in a Dairy Cooperative in Upper Northern Thailand. The research instrument used to collect data was an interview schedule and analysis used descriptive statistics and hypothesis testing by stepwise multiple regression analysis. It was found that most of sampled farmers decided to expand their dairy farming operations. Independent variables—namely, age, experience of dairy farming, practice of dairy farming, satisfaction with government including dairy farming, expectation towards children inheriting the dairy farm, and physical and economic problems in dairy farming were statistically related at the .05 level of significance to decision making by dairy farmers on occupational development. The significant problems identified by dairy farmers were: lack of land, insufficient income, lack of dairy information, and the rising cost of production. Agencies involved should: visit farms to advise farmers closely and continually, support farm loans for farm expansion, build a positive attitude towards dairy farming in farmers' children, and campaign for an increase in milk consumption, so that Thai dairy farmers are able to live sustainably.